Permeability imaging in cerebrovascular diseases: applications and progress in research. Issue 1 (December 2016) - Chen, Hui; Liu, Nan; Li, Ying; Chen, Fei; Zhu, Guangming
Abstract Cerebrovascular disease is currently the second most common cause of death after ischemic heart disease. In this article, we mainly focus on the application of permeability imaging in cases of ischemic and hemorrhagic stroke, and cerebral small vessel disease. In this review, we discuss the application of permeability imaging in ischemic stroke from two aspects: 1) for the prediction of hemorrhagic transformation after infarction, and 2) for the evaluation of newborn secondary and tertiary collateral circulations. Quantitative measurements of blood–brain barrier (BBB) disruption by the Dynamic Contrast Enhance MR (DCE-MR) can reveal the severity of intracranial hemorrhage (ICH)-induced brain damage, and that the technique has the potential to be used for testing the efficacy of interventions aimed at reducing tissue damage around the hematoma. Currently, DCE-MR is mostly applied for the assessment of tumors in patients. There is less research focused on the evaluation of mild BBB defects in normal or abnormal aging brains, dementia, or cerebral small vessel disease. More work needs to be done to select the appropriate contrast agents and decide their doses, as well as to identify methods for parameter collection and data analysis.